Advances in RNAi-Assisted Strain Engineering in Saccharomyces cerevisiae - Chen, Yongcan; Guo, Erpeng; Zhang, Jianzhi; Si, Tong (Frontiers in Bioengineering and Biotechnology, 2020)
Saccharomyces cerevisiae is a widely used eukaryotic model and microbial cell factory. RNA interference (RNAi) is a conserved regulatory mechanism among eukaryotes but absent from S. cerevisiae. Recent reconstitution of RNAi machinery in S. cerevisiae enables the use of this powerful tool for strain engineering. Here we first discuss the introduction of heterologous RNAi pathways in S. cerevisiae, and the design of various expression cassettes of RNAi precursor reagents for tunable, dynamic, and genome-wide regulation. We then summarize notable examples of RNAi-assisted functional genomics and metabolic engineering studies in S. cerevisiae. We conclude with the future challenges and opportunities of RNAi-based approaches, as well as the potential of other regulatory RNAs in advancing yeast engineering.